Border Reconfigurations in Contagious Societies. Epidemics as Biopolitical Crises from the Decameron to Nemesis (Altre Modernità, 2022)
This article aims at investigating two narratives about historical moments of sociopolitical, economic, and cultural crisis represented through literary descriptions of epidemics. I will focus on the subtext of the plague in one of the foundational texts of the Western canon, the Decameron, paying particular attention to the metaphor of contagion as a phenomenon allowing for the renegotiations of biopolitical borders in the Florentine society of the Trecento. Building on images of contamination as vehicles of contagion, I am interested in interrogating the roots and scope of the reconsideration of traditional norms and accustomed practices that Giovanni Bocaccio frames in biopolitical terms in the description of the 1348 plague in Florence. I will also take into consideration Philip Roth’s 2010 novel Nemesis, which is set against the background of the polio outbreak in Newark in 1944. Nemesis depicts a prophylactic measure identical to the country retreat that famously frames the main narrative in the Decameron, yet in Roth’s novel it represents a failed attempt to escape contagion. Another narrative trait that Nemesis shares with the Decameron is the context: a society on the verge of essential transformations in the political, cultural, and economic realm. Indeed, mercantile Florence of the Trecento was on the brink of a new era, the Early Modern period, likewise 1944 USA was involved in WWII, fighting for the geopolitical supremacy over a new world order (the Cold War) and shaping a new socio-economic model: neoliberalism.